Knowledge, Information and Surprise - Margarita Vazquez (tripleC: Communication, Capitalism & Critique)
In this paper, I analyse the paradox called The surprise exam paradox or The unexpected hanging paradox. I study some interpretations of this paradox, like Quine and Ned Hall ones, and give my own view about its solution, making some approaches from classical logic and from temporal or epistemic logic.